Pengaruh konsentrasi dan jenis larutan perendaman terhadap kecepatan ekstraksi dan sifat gel agar-agar dari rumput laut Gracilaria verrucosa - Sperisa Distantina; Devinta Rachmawati Anggraeni; Lidya Eka Fitri (Jurnal Rekayasa Proses, 2008)
Seaweeds of Gracilaria species are abundantly cultivated in Indonesia. However, studies related to its extractionprocess are still rare. In the present work, the mass transfer process on a batch extraction of agar was studied byextracting seaweeds in hot water solvent. The effect of alkali (NaOH) and acetic acid (CH3COOH) in the soakingprocess on the volumetric mass transfer coefficient (kca) and the quality of gel agar were investigated.Seaweeds (Gracilaria verrucosa) from Pekalongan coast were soaked in aqueous NaOH (1.5 N and 3.75 N) or inaqueous acetic acid solution (0.2 N, 0.6 N, and 0.8 N). After being washed, the seaweeds were extracted in hotwater of 980C and neutral pH. Some of the extract samples at various times were freezed, thawed, dried andweighed. The evaluation of experimental data showed that the mass transfer coefficient kca decreased and the gelstrength of agar increased with the increase of alkali concentration. Meanwhile, the value of kca increased andthe gel strength of agar decreased with the increase of acetic acid concentration.